Effects of static stretching on energy cost and running endurance performance - Wilson, J. M.; Hornbuckle, L. M.; Kim, J. S.; Ugrinowitsch, C.; Lee, S.-R.; Zourdos, M. C.; Sommer, B.; Panton, L. B. (The Journal of Strength and Conditioning Research, 2010)
Stretching before anaerobic events has resulted in declines in performance; however, the immediate effects of stretching on endurance performance have not been investigated. This study investigated the effects of static stretching on energy cost and endurance performance in trained male runners. Ten trained male distance runners aged 25 ± 7 years with an average V'O2max of 63.8 ± 2.8 ml/kg/min were recruited. Participants reported to the laboratory on 3 separate days. On day 1, anthropometrics and V'O2max were measured. On days 2 and 3, participants performed a 60-minute treadmill run randomly under stretching or nonstretching conditions separated by at least 1 week. Stretching consisted of 16 minutes of static stretching using 5 exercises for the major lower body muscle groups, whereas nonstretching consisted of 16 minutes of quiet sitting. The run consisted of a 30-minute 65% V'O2max preload followed by a 30-minute performance run where participants ran as far as possible without viewing distance or speed. Total calories expended were determined for the 30-minute preload run, whereas performance was measured as distance covered in the performance run. Performance was significantly greater in the nonstretching (6.0 ± 1.1 km) vs. the stretching (5.8 ± 1.0 km) condition (p < 0.05), with significantly greater energy expenditure during the stretching compared with the nonstretching condition (425 ± 50 vs. 405 ± 50 kcals). Our findings suggest that stretching before an endurance event may lower endurance performance and increase the energy cost of running.